2011
DOI: 10.1007/s10661-011-2278-1
|View full text |Cite
|
Sign up to set email alerts
|

An air quality balance index estimating the total amount of air pollutants at ground level

Abstract: A new index named Air Quality Balance Index (AQBI), which is able to characterise the amount of pollution level in a selected area, is proposed. This index is a function of the ratios between pollutant concentration values and their standards; it aims at identifying all situations in which there is a possible environmental risk even when several pollutants are below their limit values but air quality is reduced. AQBI is evaluated by using a high-resolution three-dimensional dispersion model: the air concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Research methodologies that have been employed in relation to impervious surfaces include the land use approach (Sharma, Ghosh, & Joshi, 2013) and accessing the population (Lu & Weng, 2006). Urban planning and land use approaches (Chen & Yu, 2016;Xiao et al, 2018), urban green space planning (Zhang et al, 2017) and also urban environmental assessment Trivero et al, 2012) have been used in urban impervious surface research. Sinha et al (2016) found that urban builtup land applies high reflection on SWIR and TIR wavelengths and low reflection on NIR.…”
Section: Introductionmentioning
confidence: 99%
“…Research methodologies that have been employed in relation to impervious surfaces include the land use approach (Sharma, Ghosh, & Joshi, 2013) and accessing the population (Lu & Weng, 2006). Urban planning and land use approaches (Chen & Yu, 2016;Xiao et al, 2018), urban green space planning (Zhang et al, 2017) and also urban environmental assessment Trivero et al, 2012) have been used in urban impervious surface research. Sinha et al (2016) found that urban builtup land applies high reflection on SWIR and TIR wavelengths and low reflection on NIR.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of methods for air quality research are put forward by domestic and foreign scholars: (1) using fuzzy logic to deal with air quality indicators [24] and neural networks to forewarn air pollution [25] and so on. e AQBI (Air Quality Balance Index) is used to assess air quality and environment in a three-dimensional diffusion model [26], in addition to distance discrimination, matter element analysis, breakpoint regression analysis, parting model, and so on [27]; (2) in the background of the development, we use the statistics of Weibo (microblog), DMSP/OLS (Defense Meteorological Satellite Program/Operational Linescan System), "World Map," and other methods to study on the urban air quality [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, there are many other numerical modeling and analytical methods such as GEOS-Chem chemical transport model 12 24 25 26 27 28 29 30 31 32 33 34 , Weather Research and Forecasting model coupled with chemistry (WRF/Chem) 29 35 36 37 , land-use regression (LUR) models 38 39 40 41 , Dust REgional Atmospheric Model 42 , observation-based model 43 , GIS-based multi-source and multi-box modeling 44 , global sensitivity analysis method 45 , and episode-based evolution pattern analysis 46 . In addition to using such methods to characterize the amount of pollution level in selected areas, the enhanced air quality index (AQI) can also be used 47 48 49 , such as in the form of pollutant concentration values divided by their standards 50 . The air pollution monitoring networks have been greatly improved worldwide in recent years with increased and updated sites 51 52 .…”
mentioning
confidence: 99%